VD_FINDINFO Jug / 2016 / 71 vom 10. Februar 2016 - VD Tribunal cantonal (2016)
APPRÉCIATION DES PREUVES, CIRCULATION ROUTIÈREDROIT DE LA CIRCULATION ROUTIÈRE | 286 CP, 90 al. 1 LCR, 95 al. 1 let. b LCR, 115 LEtr